CULTURAL CONSEQUENCES OF GLOBALIZATION. MAJOR CONTEMPORARY THEORIES ON THE GLOBALLOCAL INTERFERENCE - GABRIELA DUMBRAVĂ (Annals of the University of Petrosani: Economics)
The paper approaches the phenomenon of globalization from the perspective of the theories set forth by two leading 21st century figures in the field of global studies, namely Roland Robertson and Geoge Ritzer. By bringing together theoretical concepts and concrete examples from contemporary reality, this study attempts to point out that, depending on the relation between its driving forces, globalization can be either an integrative process, based on understanding, respecting and embracing diversity, or an act of leveling colonization.